The Evolution Of The University Textbook For Teaching Functional Writing Skills In Saudi Universities/ ØªØ·ÙˆØ± Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø¬Ø§Ù…Ø¹ÙŠ Ø§Ù„Ù…Ù‚Ø±Ø± Ù„ØªØ¯Ø±ÙŠØ³ Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø§Ù„ÙˆØ¸ÙŠÙÙŠØ© ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø³Ø¹ÙˆØ¯ÙŠØ© - AlMugim, Tarig Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study reveals the most prominent features of the development of university books related to teaching functional writing skills by comparing two books, the first